Chronic ulcerative jejunitis without symptoms. Issue 641 (March 1979) - Kane, S. P.; Parkins, R. A.
Abstract : A patient is presented who, in addition to subtotal villous atrophy, had superficial ulcers of the jejunum, as well as a wide band of granulation tissue deep to the crypts suggesting recurrent past ulceration. In spite of these changes she had no intestinal symptoms at the time of her presentation with reflux oesophagitis, and her only nutritional abnormality was a mild folate deficiency. Withdrawal of dietary gluten produced some improvement of the jejunal mucosa but this was not sustained on continued low-grade ingestion. She has containued to be virtually symptom-free over a 3-year period of follow-up.